Enhancement of physiology via adaptive transcription - Lissek, Thomas (Pflügers Archiv, 2025)
The enhancement of complex physiological functions such as cognition and exercise performance in healthy individuals represents a challenging goal. Adaptive transcription programs that are naturally activated in animals to mediate cellular plasticity in response to stimulation can be leveraged to enhance physiological function above wild-type levels in young organisms and counteract complex functional decline in aging. In processes such as learning and memory and exercise-dependent muscle remodeling, a relatively small number of molecules such as certain stimulus-responsive transcription factors and immediate early genes coordinate widespread changes in cellular physiology. Adaptive transcription can be targeted by various methods including pharmaceutical compounds and gene transfer technologies. Important problems for leveraging adaptive transcription programs for physiological enhancement include a better understanding of their dynamical organization, more precise methods to influence the underlying molecular components, and the integration of adaptive transcription into multi-scale physiological enhancement concepts.
Online veröffentlicht: 01 November 2024
Gesehen am 21.03.2025